Terrestrial nitrogen cycle simulation with a dynamic global vegetation model - XU‐RI; I. C. PRENTICE (Global Change Biology, 2008)
A global scale Dynamic Nitrogen scheme (DyN) has been developed and incorporated into the Lund–Posdam–Jena (LPJ) dynamic global vegetation model (DGVM). The DyN is a comprehensive process‐based model of the cycling of N through and within terrestrial ecosystems, with fully interactive coupling to vegetation and C dynamics. The model represents the uptake, allocation and turnover of N in plants, and soil N transformations including mineralization, N 2 fixation, nitrification and denitrification, NH 3 volatilization, N leaching, and N 2 , N 2 O and NO production and emission. Modelled global patterns of site‐scale nitrogen fluxes and reservoirs are highly correlated to observations reported from different biomes. The simulation of site‐scale net primary production and soil carbon content was improved relative to the original LPJ, which lacked an interactive N cycle, especially in the temporal and boreal regions. Annual N uptake by global natural vegetation was simulated as 1.084 Pg N yr −1 , with lowest values −2 yr −1 (polar desert) and highest values in the range 24–36.5 g N m −2 yr −1 (tropical forests). Simulated global patterns of annual N uptake are consistent with previous model results by Melillo et al. The model estimates global total nitrogen storage potentials in vegetation (5.3 Pg N), litter (4.6 Pg N) and soil (≥67 Pg as organic N and 0.94 Pg as inorganic N). Simulated global patterns of soil N storage are consistent with the analysis by Post et al. although total simulated N storage is less. Deserts were simulated to store 460 Tg N (up to 0.262 kg N m −2 ) as NO 3 − , contributing 80% of the global total NO 3 − inventory of 580 Tg N. This model result is in agreement with the findings of a large NO 3 − pool beneath deserts. Globally, inorganic soil N is a small reservoir, comprising only 1.6% of the global soil N content to 1.5 m soil depth, but the ratio has a very high spatial variability and in hot desert regions, inorganic NO 3 − is estimated to be the dominant form of stored N in the soil.